Pengaruh Kualitas Produk, Shopping Lifestyle, dan Visual Merchandising Terhadap Keputusan Pembelian (Studi Kasus Produk Eiger) - Vicalina Trinatalia Pasaribu; Achmad Zaky Yamani; Fauzan Romadlon (J-MAS (Jurnal Manajemen dan Sains), 2022)
Competition for fashion brand trends between companies that are increasingly stringent has an impact on consumer needs for quality and varied products. This is due to decreased consumer interest in the superiority of goods that are not in accordance with the lifestyle of consumers. This study aims to identify the influence of product quality, shopping lifestyle, and visual merchandising on purchasing decisions for Eiger products in Purwokerto. This study uses quantitative methods. The collected data was tested statistically using multiple regressions. This study shows that the demographic factors of respondents have a significant assessment of purchasing decisions. The demographic factors are gender, age, college origin, pocket money and products used. The results of this study indicate that the variables of product quality, shopping lifestyle, and visual merchandising simultaneously affect the purchasing decisions of Eiger products. While partially, the results of product quality have no significant effect, so it still requires evaluation of product improvements. The better the quality of the product, the more attractive the consumer's attraction to buying the product.